Effectiveness of the retreatment of patients with multibacillary leprosy and episodes of erythema nodosum leprosum and/or persistent neuritis: A single-center experience - Lastória, Joel Carlos [UNESP]; Putinatti, Maria Stella de Mello Ayres [UNESP]; de Almeida, Thaís Sampaio Corrêa [UNESP]; Padovani, Carlos Roberto [UNESP] (FapUNIFESP (SciELO), 2018)
Background: Erythema nodosum leprosum may appear before, during or after treatment of leprosy and is one of the main factors for nerve damage in patients. When it occurs or continues to occur after treatment, it may indicate disease recurrence and a new treatment may be instituted again. Objective: To evaluate the retreatment of patients with multibacillary leprosy who underwent standard treatment with multidrug therapy, but developed or continued to present reactions of erythema nodosum leprosum and/or neuritis 3-5 years after its end. Method: For this objective, a new treatment was performed in 29 patients with multibacillary leprosy who maintained episodes of erythema nodosum and/or neuritis 3-5 years after conventional treatment. Results: In general, we observed that 27 (93.10%) had no more new episodes after a follow up period of eight months to five years. In five of these patients the reason for the retreatment was the occurrence of difficult-to-control neuritis, and that has ceased to occur in all of them. Study limitations: Small number of patients. Conclusion: In the cases observed, retreatment was an effective measure to prevent the occurrence of erythema nodosum leprosum and/or persistent neuritis.
Keywords: Erythema nodosum; Leprosy; Neuritis; Retreatment